The Correlation of Caries Risk Assessment with Oral Hygiene Index and Parent’s Education Level in Pesantren Mizanul Ulum Sanrobone - Fadil Abdillah Arifin; Mila Febriany; Ilmianti Ilmianti (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2023)
Attention must be given to the boarding school students' oral health status.  There is a considerable probability that boarding school students' oral cavities are going to suffer a variety of problems, particularly when they live and stay away from their parent's supervision. Caries risk assessment is used to predict and prevent the development of caries. This study aims to determine the correlation between caries risk assessment with oral hygiene status and parents’ education level in Pesantren Mizanul Ulum Sanrobone. Dental examinations and interviews were conducted on 61 students using the Caries Risk Assessment (CRA) form and Oral Hygiene Index Simplified (OHI-S). The correlation between caries risk assessment and oral hygiene status and the education level of students' parents was assessed using the Spearman test. According to the statistical analysis findings, there was a 0.312 correlation coefficient (r) between the CRA and the OHI-S. Meanwhile, the parents of the students have an education level of -0.198. These results showed a correlation between caries risk assessment and oral hygiene status (OHI-S), and no correlation with the education level of students’ parents. According to these findings, students are more likely to get cavities if their oral hygiene is poor.